Transcription regulation of sex-biased genes during ontogeny in the malaria vector Anopheles gambiae. - Kalle Magnusson; Antonio M Mendes; Nikolai Windbichler; Philippos-Aris Papathanos; Tony Nolan; Tania Dottorini; Ermanno Rizzi; George K Christophides; Andrea Crisanti (PLoS ONE)
In Anopheles gambiae, sex-regulated genes are responsible for controlling gender dimorphism and are therefore crucial in determining the ability of female mosquitoes to transmit human malaria. The identification and functional characterization of these genes will shed light on the sexual development and maturation of mosquitoes and provide useful targets for genetic control measures aimed at reducing mosquito fertility and/or distorting the sex ratio.We conducted a genome wide transcriptional analysis of sex-regulated genes from early developmental stages through adulthood combined with functional screening of novel gonadal genes. Our results demonstrate that the male-biased genes undergo a major transcription turnover starting from larval stages to adulthood. The male biased genes at the adult stage include a significant high number of unique sequences compared to the rest of the genome. This is in contrast to female-biased genes that are much more conserved and are mainly activated during late developmental stages.The high frequency of unique sequences would indicate that male-biased genes evolve more rapidly than the rest of the genome. This finding is particularly intriguing because A. gambiae is a strictly female monogamous species suggesting that driving forces in addition to sperm competition must account for the rapid evolution of male-biased genes. We have also identified and functionally characterized a number of previously unknown A. gambiae testis- and ovary-specific genes. Two of these genes, zero population growth and a suppressor of defective silencing 3 domain of the histone deacetylase co-repressor complex, were shown to play a key role in gonad development.